Major coherences of the impacts of innovations on space structure - Ökrös , Imre; Nagy, Henrietta; Káposzta, József (Studia Mundi – Economica, 2016)
The impacts of innovations on space structure are in the focus of interest nowadays, since the moderation of spatial differences is a priority for each national government. Many deal with this urging spatial development problem that is in relation to the major problems of cities by now. One reason for seeking better economic conditions and strategies was the finding that regional recession might be gradual and the economic and social crisis might not be avoided. Innovative developments are more and more promoted because the economic basis of the Western-European states is risked by the tight competition and technological shift. Overall, it can be seen clearly that regional developments based on the introduction of innovations can bring long-term solutions for the changes in spatial structure.